Cultura e ambivalenza - Giorgio Grossi (Quaderni di Sociologia, 2017)
Starting from the perspective of ambivalence, as a different way of interpreting social interaction, I propose to use this dual category to analyze contemporary cultural processes. If we observe the phenomenology of the so-called “cultural field” within our globalized world, we must point out two connected trends: first, a changeable profile of second modernity culture, which appears always more hybrid, de-territorialized and hypertrophic (that is, with plural significance, territorial dis-embedding and unlimited imaginative creation); second, this change is related to a disjunction within social structure between the economic and political system, and the cultural system, as argued, in different way, by D. Bell and A. Appadurai. In this perspective, culture becomes typically ambivalent at a double level: with reference to the other subsystems (through a growing autonomy) and referring to the cultural field itself (through a flourishing of possible and personal meanings). We can, therefore, postulate a “weak culture” as a new dimension of contemporary cultural field, able to take in account multiculturalism as well as individualization.